The Right to Truth in the Digital Age: Disinformation, Democracy, and the Limits of Legal Protection - Kilanowski, Marcin (PRAWO i WIĘŹ, 2025)
In an era marked by rapid technological advancement and the proliferation of digital platforms, the boundaries between truth, opinion, and disinformation have become increasingly blurred. This paper critically examines the misuse of modern communication technologies and their implications for privacy, knowledge acquisition, and democratic governance. It explores how filter bubbles, data profiling, and algorithmic manipulation empower corporations, political actors, and governments to shape public opinion and suppress dissent. Against this backdrop, the paper questions whether a universal “right to truth” can serve as a viable legal principle or whether such a construct risks legitimizing censorship and authoritarian control. Drawing from philosophical critiques – particularly those of Michel Foucault and J.S. Mill – the paper argues that truth is best approached not as a static right, but as a continuous process supported by freedom of speech, access to education, and institutional safeguards. Ultimately, it calls for the development of dynamic legal, educational, and technological strategies that enable societies to resist disinformation, protect privacy, and foster an informed public capable of engaging in truth-seeking dialogue.